Practical guide for the implementation of HSEQ management systems (Orinoquia, 2021)
The practical guide for the implementation of HSEQ management systems allows in a simple, clear, precise and practical way, through the experience of the authors, to provide an operational structure for the implementation of management systems that allows planning and organizing groups of work necessary for this purpose, through a standard implementation model of ten big steps. No standard by itself has an explanation of where and how to start implementing management systems, nor an example of the documented information necessary to respond to the specified requirements, which is why it is essential to define a common thread so that Any company of any size and sector in Colombia, sees the implementation of these process management standards as an opportunity for growth and a sustained increase in its level of maturity. With this research, it was intended to design a methodological guide for the implementation of integrated HSEQ management systems in organizations of the productive sector for two years. For the collection and analysis of information, this research adopted the method ofobserving a phenomenon by analyzing the processes set in motion by each of the researchers as their own experience in their sector of activity. In this way, the following results were obtained: a. From the result of the standard model of ten big steps for the implementation of HSEQ management systems. b. From the evaluation of the model of ten big steps of the HSEQ systems, through the implementation of the SG-SST in the Embajador del Llano hotel, located in the city of Villavicencio - Meta, with 81.44% compliance with the regulatory requirements. c. From the organizational impact that the Ten Big Steps model has had on the company Almacen y Taller Rectiamerica, with a 30% increase in productivity, profitability by 10%, 93% in the level of customer satisfaction, rate reduction of guarantees at an average of 2% per year, and disposition of a total of 13.35 tons of metallic material in three years. In this way, the guide for the implementation of integrated systems is an innovative, practical and accessible way to implement integrated systems based on its 10-step model that offers the reader a dynamic anduseful tool in companies in Colombia.
Keywords: model; implementation; standardization; efficiency; guide